2019
DOI: 10.25259/jcis-38-2019
|View full text |Cite
|
Sign up to set email alerts
|

Transabdominal Ultrasonography in Symptomatic Choledocholithiasis – Usefulness in Settings with Limited Resources

Abstract: Objective: Ultrasonography remains the initial imaging modality in the management of biliary disease. This study is designed to evaluate the accuracy of transabdominal ultrasonography in diagnosing biliary pathology in patients with choledocholithiasis. Methods: This was a retrospective study of a continuous sample of patients over a period of 3 years ending in January 2016; these patients were referred for endoscopic management of choledocholithiasis to a tertiary care hospital in Colombo, Sri Lanka. Ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
3
4
0
1
Order By: Relevance
“…In this study, we used the univariate and multivariate logistic regression analysis to determine the predictive factors for CBD stone. Our results revealed that multiple gallbladder stones, the maximal diameter of CBD stone measured by preoperative ultrasonography, preoperative GGT level and DB/TB ratio were independent predictors of CBD stone, which had been reported by previous studies [17][18][19]. * US, Ultrasonography; US Positive indicates that imaging examination revealed CBD stone; CBDD, the value of maximal CBD dimeter measured on the Ultrasonography; ALT, alanine aminotransferase; AST, aspartate aminotransferase; ALP, alkaline phosphatase; GGT, glutamyl transpeptidase; TB, total bilirubin; DB, direct bilirubin; HR, hazard ratio; CI, confidence interval; P-value<0.05 indicates statistical significance.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, we used the univariate and multivariate logistic regression analysis to determine the predictive factors for CBD stone. Our results revealed that multiple gallbladder stones, the maximal diameter of CBD stone measured by preoperative ultrasonography, preoperative GGT level and DB/TB ratio were independent predictors of CBD stone, which had been reported by previous studies [17][18][19]. * US, Ultrasonography; US Positive indicates that imaging examination revealed CBD stone; CBDD, the value of maximal CBD dimeter measured on the Ultrasonography; ALT, alanine aminotransferase; AST, aspartate aminotransferase; ALP, alkaline phosphatase; GGT, glutamyl transpeptidase; TB, total bilirubin; DB, direct bilirubin; HR, hazard ratio; CI, confidence interval; P-value<0.05 indicates statistical significance.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we used the univariate and multivariate logistic regression analysis to determine the predictive factors for CBD stone. Our results revealed that multiple gallbladder stones, the maximal diameter of CBD stone measured by preoperative ultrasonography, preoperative GGT level and DB/TB ratio were independent predictors of CBD stone, which had been reported by previous studies [17][18][19]. Based on the these variables, we developed a nomogram model and the results…”
Section: Discussionsupporting
confidence: 71%
“…This is often detected when introducing the optic and observing that it is not in the abdominal cavity, making it necessary to communicate this space with the intra-abdominal space. (16,17,18) 2 -Typical of Pneumoperitoneum:…”
Section: Insufflation -Gas Insufflation Into the Abdominal Wall Mesen...mentioning
confidence: 99%
“…Poznati Šarkoov trijas akutno nastalog bola u gornjem desnom kvadrantu, groznice i ikterusa, klinički ukazuje na akutno nastalu bilijarnu opstrukciju sa razvojem ascendentnog holangitisa. Iako je ultrazvuk visoko senzitivan i specifičan u detekciji kalkuloze žučne kese, njegova uloga u evaluaciji holedoholitijaze i druge bilijarne patologije nije precizno definisana, budući da su Slika 1: Akutni kalkulozni holecistitis -patološka distenzija lumena žučne kese u kojem se vide kalkulusi (inklaviran u vratu -zvezdica) uz zadebljao i raslojen zid (strelica) druge metode, poput magnetno rezonantne holangiopankreatografije (MRCP) i endoskopske retrogradne holangiopankreatografije (ERCP), preciznije 7 . Dilatacija intrahepatičnih žučnih puteva ukazuje na bilijarnu opstrukciju i lako se detektuje ultrasonografski, jer su nedilatirani žučni putevi promera 1 do 2 mm i teško se vizuelizuju, navodeći radiologa na detekciju uzroka same opstrukcije 2 .…”
Section: Akutna Bilijarna Opstrukcija I Akutni Ascendentni Holangitisunclassified